20.4k views
3 votes
Solve using elimination method

11x + 9y = -5
7x + 5y = -1

User Poyraz
by
4.9k points

1 Answer

7 votes

Answer: (2,-3)

Explanation:

To solve by elimination method, we need to choose which variable to eliminate. Let's eliminate y. We need to make sure that the y coefficients in both equations are equal. To do that, you multiply the first equation by 5 and the second by 9.

(11x + 9y = -5)5 [multiply entire equation by 5]

(7x + 5y = -1)9 [multiply entire equation by 9]

--------------------------------------------------------------------------------------------------------

55x+45y=-25

63x+45y=-9

Now that the y are both the same, we can eliminate y by subtracting both equations and solve.

-8x=-16 [divide both sides by -8]

x=2

Now that we have x=2, we can plug that in to any equation to find y.

7(2)+5y=-1 [multiply]

14+5y=-1 [subtract both sides by 14]

5y=-15 [divide both sides by 5]

y=-3

With the y-value, we know that the answer is (2,-3).

User Jinna Baalu
by
5.1k points